2002
DOI: 10.1007/s00213-002-1090-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the nitric oxide donor molsidomine on different memory components as assessed in the object-recognition task in the rat

Abstract: These results indicate that the NO donor molsidomine may modulate different aspects of memory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…in a volume of 0.5 ml per rat. Doses of molsidomine were chosen based on studies in which they were effective against learning impairments and did not produce adverse side effects (hypotension, sensorimotor deficits) (Meyer et al, 1998; Pitsikas et al, 2001, 2002a, b, 2003, 2005). Doses of compounds are expressed as bases.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…in a volume of 0.5 ml per rat. Doses of molsidomine were chosen based on studies in which they were effective against learning impairments and did not produce adverse side effects (hypotension, sensorimotor deficits) (Meyer et al, 1998; Pitsikas et al, 2001, 2002a, b, 2003, 2005). Doses of compounds are expressed as bases.…”
Section: Methodsmentioning
confidence: 99%
“…Among NO donors, molsidomine has a high bioavailability, a long‐lasting duration of action (Boger et al, 1994) likely crosses the blood‐brain barrier (BBB) (Maccario et al, 1997; Rigamonti et al, 2001) and increases its permeability (Mayhan, 2000). Molsidomine was found effective to antagonize memory deficits in different animal models (Meyer et al, 1998; Pitsikas et al, 2001, 2002a, b, 2003, 2005).…”
mentioning
confidence: 99%
“…This could lead to overlearning of environmental cues and contamination of the task by reference memory. To try to prevent this phenomenon, we chose a 24-h intertrial delay because it was previously shown that this duration made discrimination more difficult for control rats (63).…”
Section: Object Recognitionmentioning
confidence: 99%
“…Normally, animals can discriminate between familiar and novel objects (exploration, novel > familiar object) at T2 30‐min . However, discrimination is generally attenuated at T2 24‐h (similar exploration duration for both the objects) (Ennaceur et al, ; Bartolini et al, ; Pitsikas et al, ). In the present study also, untreated control rats showed intact memory at T2 30‐min , but deficit at T2 24‐h .…”
Section: Discussionmentioning
confidence: 99%